Changes in Respiration, Composition and Sensory Characteristics of Rambutan Packed with Plastic Films During Storage at Low Temperature - Widjanarko, Simon B.; Trisnawati, CH. Yayuk; Susanto, Tri (Jurnal Teknologi Pertanian, 2000)
Rambutan were held in sealed propropylene, polyethylene film bags and unpacked at 10±1 oC and 90-95% RH for 12 days. Physico-chemical, sensory changes and COEvolved were observed after 2, 4, 6, 8, 10 and 12 days. Packing fruit in plastic bagsreduced declining quality by means of weigh loss, moisture content, reduction sugarscontent and vitamin C. Packed fruit showed low respiration rate, low browning rate andhigh retaining total phenol in rambutan skin. Treated fruit also indicated better attributesassociated with eating quality than control fruit. Polypropelene plastic bags showed thebest result in all changes quality occurring during storage at low temperature observed. Keyword: rambutan, pakced fruit, storage